ChemInform Abstract: Grain Boundaries in Nanocrystalline Catalytic Materials as a Source of Surface Chemical Functionality. Issue 4 (January 2015) - Landau, Miron V.; Vidruk, Roxana; Vingurt, Dmitro; Fuks, David; Herskowitz, Moti
Abstract Review: 86 refs.